Сучасні волоконні інтерферометри - Саєнко, Є. О. (ХНУРЕ, 2023)
The purpose of this report is to consolidate knowledge related to the main physical processes that take place in modern fiber interferometers, the history of their origin, the structure of these devices, the principle of their operation, the main parameters and characteristics, and their application in various fields. The main types of modern fiber interferometers, namely the Mach-Zehnder, Fabry-Perot and Michelson interferometers, are considered